2018
DOI: 10.1002/jia2.25050
|View full text |Cite
|
Sign up to set email alerts
|

How far are we from viral hepatitis elimination service coverage targets?

Abstract: IntroductionIn 2016, the Global Health Sector Strategy (GHSS) on viral hepatitis called for elimination of viral hepatitis as a major public health threat by 2030 (i.e. 90% reduction in incidence and 65% in mortality). In 2017, WHO's first‐ever Global Hepatitis Report presented the baseline values for each of the core indicators of the strategy. We review the challenges and opportunities that lie ahead in order to reach the 2030 service coverage targets.DiscussionThree‐dose coverage of hepatitis B vaccine in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 25 publications
0
52
0
2
Order By: Relevance
“…With the identification of those infected becoming probably the leading challenge for HCV response in the MENA region and elsewhere, we aimed to address who should be tested for HCV so that test and treat programs could be scaled up efficiently and effectively, targeting those most likely to be carriers. Against a dearth of studies on HCV testing in LMICs, we addressed specific questions for the MENA region: (1) Which populations are at higher risk of having been exposed and therefore should be tested? (2) What are the yields of a testing program targeting different populations?…”
mentioning
confidence: 99%
“…With the identification of those infected becoming probably the leading challenge for HCV response in the MENA region and elsewhere, we aimed to address who should be tested for HCV so that test and treat programs could be scaled up efficiently and effectively, targeting those most likely to be carriers. Against a dearth of studies on HCV testing in LMICs, we addressed specific questions for the MENA region: (1) Which populations are at higher risk of having been exposed and therefore should be tested? (2) What are the yields of a testing program targeting different populations?…”
mentioning
confidence: 99%
“…Hepatitis B virus (HBV) is a major causative agent of chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC) . With an estimated 257 million chronic carriers worldwide, HBV infection remains to be one of the major health problems. HBV belongs to the Hepadnavividae family and contains different forms of genome in virions.…”
mentioning
confidence: 99%
“…The timely BDV poses many logistical challenges; its global coverage is still estimated to be only 40% and is highly heterogeneous between regions. The Western Pacific region managed to increase the coverage of BDV from 2% in 2000 to 83% in 2015, which was credited to a regional commitment and goal for control of HBV infection . In sharp contrast, in the African region, only 12 countries have integrated BDV into national policy with reported regional coverage level of only 10%.…”
Section: Interventions To Prevent Mother‐to‐child Transmission Of Hbvmentioning
confidence: 99%
“…The Western Pacific region managed to increase the coverage of BDV from 2% in 2000 to 83% in 2015, which was credited to a regional commitment and goal for control of HBV infection. 38 In sharp contrast, in the African region, only 12 countries have integrated BDV into national policy with reported regional coverage level of only 10%. Moreover, even in countries that integrated BDV, studies have revealed the lack of compliance with the timeliness.…”
Section: Timely Birth Dose Vaccinationmentioning
confidence: 99%